Analisis Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Ekonomi Syariah Angkatan 2023 Terhadap Pembukaan Rekening Bank Syariah - Restini, Astri Dwi; Nikmatika, Anisa; Khiar, fadla Nurul; Maulana, Satria (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2024)
Islamic banks in Indonesia began to develop after the Indonesian Ulema Council (MUI) decided in the early 1990s to establish a financial system in line with Islamic sharia. The first Islamic bank, Bank Muamalat Indonesia, began operations on May 1, 1992. Affirming fair transactions, promoting ethical and halal business practices, and prohibiting usury, speculative activities, and uncertainty are all principles of Sharia law, which the bank aims to uphold through its services. This quantitative study aimed to identify the relationship between pre-existing characteristics, including service quality, student trust, bank location, and attitudes toward Islamic banking. The purpose of this study was to identify variables influencing the choice to create and save in an Islamic account among Islamic Economics students at Sultan Agen Tirtayasa University in the class of 2023. A 5% margin of error was applied to the total number of respondents when the Slovin method was used to determine the sample. A survey was sent to the Islamic Economics class of 2023 to collect data. The survey findings highlight the important role of Islamic banks in facilitating savings, production, consumption, and trade.